Exploring the relation between spirituality and gratitude in a Spanish sample of nursing students - Fernández-Pascual, María Dolores (Journal for the Study of Spirituality, 2025)
Previous findings have reported the positive benefits of spirituality and gratitude, and their links to physical and mental health. To date, little is known concerning the relationship between spirituality and gratitude and its effectiveness in the training and practice of nursing. A cross-sectional correlational study design was used to analyse the relationship between spirituality, gratitude, and a set of criteria variables in a nursing student sample. A convenience sample of n = 187 nursing students at the University of Alicante (Spain) who were enrolled in the teaching subject of Psychology participated in this study. Data were collected in 2022–2023 using self-report questionnaires, Spirituality (the short form of the Spanish version of the Meaning in Life Scale, MiLS-sp/sf) and the Spanish version of the Gratitude Questionnaire. Another six variables were used to assess the following aspects: self-assessments of health, quality of life (general and recent), personal happiness, religiosity, and belief in the afterlife. The data were analysed using descriptive and relational statistics. Our results indicate a modest positive relationship between the level of gratitude and spirituality. Out of the four meanings of spirituality, Peace is the construct most correlated to gratitude. These findings suggest that incorporating spirituality and gratitude into nursing education could enhance students’ well-being and professional practice.